2008
DOI: 10.1074/jbc.m806351200
|View full text |Cite
|
Sign up to set email alerts
|

Residue 17 of Sauvagine Cross-links to the First Transmembrane Domain of Corticotropin-releasing Factor Receptor 1 (CRFR1)

Abstract: Corticotropin-releasing factor (CRF), 2 the main regulator of the hypothalamic pituitary adrenal axis (1), binds to specific G protein-coupled receptors CRFR1 (2, 3) and CRFR2 (4 -7) cloned from several mammalian and nonmammalian species. A third CRF receptor, CRFR3, was found only in fish (8). Several CRF-like peptides were shown to interact with the CRF receptors with high affinity: sauvagine (SVG) characterized from the frog skin (9), urotensin I from the urophysis of fish (10), and urocortin I (UCN1) from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 65 publications
2
14
0
2
Order By: Relevance
“…In particular, upon sauvagine binding to CRF1, residues 17 and 16 were shown to be located in close proximity to residue 117 in the extracellular portion of the TM1 and residue 257 in the second extracellular loop (EL2) of the receptor, respectively. 94,95 The latter finding is in agreement with the results of an alanine mutagenesis study, which has suggested that Trp259 and Phe260 in the EL2 of CRF1 receptor most likely interact with ligands, and specifically with the amino-terminal residues 8-10 of SVG and the corresponding ones of CRF. 96 Furthermore, this study has proposed that the interaction between the amino-terminal region of CRF family peptides and Trp259 and Phe260 of CRF1 seems to be critical for receptor activation and the subsequent appearance of a biological effect.…”
Section: Crf Receptorssupporting
confidence: 80%
“…In particular, upon sauvagine binding to CRF1, residues 17 and 16 were shown to be located in close proximity to residue 117 in the extracellular portion of the TM1 and residue 257 in the second extracellular loop (EL2) of the receptor, respectively. 94,95 The latter finding is in agreement with the results of an alanine mutagenesis study, which has suggested that Trp259 and Phe260 in the EL2 of CRF1 receptor most likely interact with ligands, and specifically with the amino-terminal residues 8-10 of SVG and the corresponding ones of CRF. 96 Furthermore, this study has proposed that the interaction between the amino-terminal region of CRF family peptides and Trp259 and Phe260 of CRF1 seems to be critical for receptor activation and the subsequent appearance of a biological effect.…”
Section: Crf Receptorssupporting
confidence: 80%
“…L42 belongs to a portion of the NTD not involved in ligand binding and was chosen as negative control, while Y73 is located in a loop domain predicted to come into close proximity to the bound ligand [10] (Figure 1). Y116 and Y270 are close to crosslinking sites identified using photoactivatable derivatives of Svg [12] and Ucn 1. [13] To ensure that the mutant receptors correctly interact with the peptide agonists, we measured the stimulated intracellular accumulation of cyclic AMP (data in SI).…”
mentioning
confidence: 99%
“…These receptors also have a large extracellular aminoterminal region (N-region) that has been structurally characterized in NMR and crystallographic studies (Grace et al, 2007;Pioszak et al, 2008;Underwood et al, 2010). The N-region and the extracellular loops of family B GPCRs have been shown to play an important role in peptide binding (Holtmann et al, 1996;Liaw et al, 1997;Perrin et al, 1998;Dautzenberg et al, 1999;Unson et al, 2002;Kraetke et al, 2005a;Grace et al, 2007;Assil-Kishawi et al, 2008;Pioszak et al, 2008;Gkountelias et al, 2009).…”
Section: Introductionmentioning
confidence: 99%